FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA UIN RADEN MAS SAID SURAKARTA DALAM BERINVESTASI SYARIAH DI BMT MAZAYA - Arfiansyah, Mufti Arief; Latifah, Nanda Nur; Amelia, Lailatul (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2023)
The purpose of this study was to determine the factors that influence the interest of UIN Raden Mas Said Surakarta students in making sharia investments at BMT Mazaya. The study used a quantitative approach with a population of UIN RMS Surakarta students. The sampling method in this study used random sampling of 100 respondents. The research instrument with a questionnaire using a Likert scale. Data analysis used multiple linear regression analysis and assisted with SPSS software. The research data was tested with validity test, reliability test, classical assumption test, and hypothesis test. The results of the study lead to conclusions that affect student interest are products that have a significant effect on interest, while promotions, places and prices have less significant effect on student interest in investing in BMT Mazaya.